Activating macrophages for enhanced osteogenic and bactericidal performance by Cu ion release from micro/nano-topographical coating on a titanium substrate. (December 2019) - Huang, Qianli; Ouyang, Zhengxiao; Tan, Yanni; Wu, Hong; Liu, Yong
Abstract: In the field of orthopaedics, inflammation-modulatory biomaterials are receiving increasing attentions due to their abilities to regulate innate immune response and mediate wound healing. In the current work, a Cu-containing micro/nano-topographical bio-ceramic surface (Cu-Hier-Ti surface) was employed as material model to explore the role played by Cu 2+ release or material surface in regulating macrophage polarization as well as macrophage-mediated osteogenic and bactericidal effect. A Cu-free micro-topographical surface (Micro-Ti surface) generated by micro-arc oxidation was employed as control. The results showed that Cu 2+ supplemented directly into the culture medium or released from Cu-Hier-Ti surface could polarize macrophages to pro-inflammatory M1 phenotype by activating Cu-transport signaling (copper transporter 1 (CTR1) and ATP7A) in macrophages, while the material characteristics exhibited anti-inflammatory effect to some extent by regulating integrin (α5, αM, β1 and β2) and TLR (TLR-3, TLR-4, Myd88 and Ticam-1/2) signaling. Macrophages grown on Cu-Hier-Ti surface or treated by Cu 2+ could create a favorable inflammatory microenvironment for osteoblast-like SaOS-2 cell proliferation and differentiation. Moreover, Cu-Hier-Ti surface promoted macrophage capacity to engulf and kill bacteria, even though it did not show direct bactericidal effect against Staphylococcus aureus. In vivo results showed that Cu-Hier-Ti surface could lead to promoted osteointegraion and enhanced expression levels of M1 surface marker CD11c, growth factor BMP-6 and osteogenic makers including osteocalcin (OCN) and Runx-2 at the biomaterial/bone tissue interface in a rat model. The results indicate that Cu could be employed as a promising inflammation-modulatory agent to activate macrophages for enhanced osteogenic and bactericidal effect. Statement of significance: The next generation of bone biomaterials should be active to regulate the local inflammatory environment such that it favors bone regeneration. For the design and development of Cu-containing inflammation-modulatory biomaterials, it is of great importance to recognize the exact role played by Cu 2+ release or material surface characteristics. So far, relatively little is known about the regulatory role of Cu 2+ or micro/nano-topographical surface on macrophages. The results in the current work suggest that Cu 2+ release and material surface characteristics of Cu-containing micro/nano-topographical coating could activate distinct signaling pathways in macrophages. The activated M1 macrophages exhibited stimulatory effect on osteoblast maturation and enhanced bactericidal capacity against Staphylococcus aureus . This study might provide new thoughts for the development of multi-functional Cu-containing biomaterials. Graphical abstract: Image, graphical abstract